Auditory performance of preschool children with hearing aids or cochlear implant in Kelantan - Marzuki, Nurul Aisyah (Universiti Sains Malaysia, 2016)
In recent years, there is no study that has been carried out to measure the effectiveness of HA or CI fitting i.e.the parents report on their child speech and language behavioural and its relation with factors that may affect the auditory performance among pre-schoolers in Malaysia specifically in Kelantan. Therefore, this study aims to determine the auditory performance of pre-school children with HAs or CI in Kelantan. Subjects were recruited from Hospital USM patient’s record and total of 11 children participated in this study. Six of them were HAs’ user while five of them where CI users. Based on the aided performance, the children were divided into three groups which consists of good average aided response (20-40 dBHL), moderate average aided response (41-60 dBHL), and poor average aided response (61-80 dBHL). Each of them was being tested using aided test, 6 Ling’s sound test and MAIS and MUSS questionnaire for the parents to score their children auditory skills and use of meaningful speech. Based on the results, there is no correlation between average aided performances and hearing age with MAIS and MUSS scores (p > 0.05). However for the correlation between Six Ling’s sound test, there was significant, moderately strong, positive correlation (Spearman’s r= 0.772) with the MAIS scores only (p < 0.05). These three groups of aided performances also shows no significant differences with MAIS and MUSS scores (p > 0.05) however for moderate average aided performance (41 -60 dBHL) shows highest median and IQR score for MAIS and MUSS, MAIS (median, 21 and IQR, 18) whereas for MUSS, (median is 22.5 and IQR 16). In conclusion, there is not much different in terms of auditory performance for children with HA’s or CL MAIS and MUSS scores on its own may not be a good predictor of child’s auditory performance as only MAIS and 6 Ling’s sound did correlate well.